Improving Students’ Vocabulary Mastery through Snake and Ladder Game at Seventh-Grade Students - Jelimun, Vinsensia Noyanti; Mukarom, Mukarom; Pusparini, Indrawati (UIBU, 2024)
This classroom action research aimed to improve seventh-grade students’ vocabulary mastery by implementing the Snake and Ladder game as an interactive learning medium. The study was conducted in two cycles following Kemmis and McTaggart’s model consisting of planning, action, observation, and reflection. Participants included 32 seventh-grade students from a junior high school in Indonesia. Data were gathered through vocabulary tests, observation checklists, field notes, and student interviews. Findings indicate that using the Snake and Ladder game enhanced students’ motivation, participation, and vocabulary achievement. Students’ scores improved from a pre-test average of 58.7 to 69.5 in Cycle 1 and later reached 81.3 in Cycle 2, surpassing the minimum mastery criterion. Qualitative findings further showed that the game encouraged collaboration, reduced anxiety, fostered a supportive learning climate, and created a joyful classroom atmosphere. These results suggest that the Snake and Ladder game is an effective instructional strategy for strengthening vocabulary mastery among seventh-grade students. Teachers are recommended to incorporate structured game-based learning activities into English lessons to improve student engagement and learning outcomes.